Use and effects of computer assited language learning on (CALL) 11th grade students at Francisco Morazán High School of David, Chiriquí, 2013 - Quintero, Keyla; Silvera, Grasse (David, Panamá : UDELAS, 2013)
Today, Panama stands at a crossroad. One hundred years have passed since the opening of Panama Canal, and this country must decide in which direction its future lies. Some people believe that it is sufficient for our country to glory in our past, and rest on our laurels.
TABLE OF CONTENT TABLE OF GRAPH TABLE OF CHART INTRODUCTION CHAPTER I BACKGROUND INFORMATION CHAPTER II: THEORETICAL FRAMEWORK 2.1. Computer programs 2.1.1. The study of Rosetta Stone as Resource in teaching 2.2. Study of BYKI (BEFORE YOU KNOW IT) as a learing resource 2.2.1. Principles of efective second language vocabulary instruction 2.2.1.1. Present new words frequently and repeatedlyin input 2.2.1.2. Use meaning-bearing comprehensible input when presenting new words 2.2.1.3. Limit forced output during the inbitial stages of learning new words 2.2.1.4. Limit forced semantic elaboration during the initial stages of learning new words 2.2.1.5. Progress from less demanding to more demanding vocabulary related activities 2.3. Study of tellmemore as a learning resource 2.3.1. Learning a language on your own with Rosetta Stone 2.4. Listening 2.5. Advantages of implementing multimedia in the classroom And other more CHAPTER III: METHODOLOGICAL FRAMEWORK CHAPTER IV: DATA COLLECTION
Incluye Table content
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- STRATEGY; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA EN INGLÉS; FRANCISCO MORAZÁN HIGH SCHOOL - CHIRIQUÍ